Increasing Antimicrobial Resistance of Vibrio cholerae O1 Biotype El Tor Strains Isolated in a Tertiary-care Centre in India (Journal of Health, Population and Nutrition, 2012)
The antimicrobial susceptibility patterns are on constant change with the recent emergence of multidrugresistant  strains of most bacteria. Results of recent studies in India showed that most isolates of Vibrio  cholerae O1 were resistant to the commonly-used antibiotics. The study was conducted to determine the  antibiotic susceptibility patterns of V. cholerae O1 isolated during 2008-2010 at the hospital of the Jawaharlal  Nehru Institute of Post Graduate Medical Education and Research, Puducherry, India. In total, 154 strains  of V. cholerae O1 from 2,658 stool specimens were reported during January 2008December 201034 in  2008, 2 in 2009, and 118 in 2010. The isolates of V. cholerae O1 were subjected to antimicrobial susceptibility  testing using the Kirby-Bauer method. The antibiotic disks tested were tetracycline (30 ?g), furazolidone  (100 ?g), ampicillin (10 ?g), ceftriaxone (30 ?g), and ciprofloxacin (5 ?g). Escherichia coli ATCC 25922  was used as the control organism. The minimum inhibitory concentrations (MICs) of ceftriaxone, ciprofloxacin,  and tetracycline were determined using the agar dilution method for all the strains. The E-test  method was used for the strains which had either intermediate resistance or were resistant to the antibiotics  by the agar dilution method. The results of the agar dilution corroborated the results of the E-test. The MIC  of ceftriaxone in 151 strains was